Disharmonisasi Pengaturan Penetapan Wilayah Pertambangan Rakyat Pada Kawasan Hutan - Paulus Bundong; Heria Mariaty; Thea Farina (Fakultas Hukum, Universitas Palangka Raya, 2022)
Legislation is a system that does not want and does not justify any conflict between the elements or parts therein. Legislation becomes overlapping because it has not been integrated and synergistic legislation that is sectoral so that it can lead to disharmonization. Disharmony of legislation is a conflict / conflict between legal norms or conflicts of authority that arise due to the enactment of legislation. Disharmony legislation is a legal problem that occurs across legal norms. Where between legal norms the one with the other legal norms that occur collision cause the inconsistency of a legal regulation. Due to the legal disharmonization of law is the occurrence of differences in interpretation in its implementation, the emergence of legal uncertainty, legislation is not implemented effectively and efficiently, legal dysfunction, meaning that in this case the law can not function to provide guidelines for behavior to the community, social control, and dispute resolution. Harmonization in law is needed for alignment, adjustment of legislation, government decisions, judge decisions, legal systems and legal principles with the aim of increasing legal unity, legal certainty, justice and equality, usefulness and clarity of law